Making Anyatha (Upper Lander) and Auktha (Lower Lander): Crossing the Introduction of the Colonial Boundary System to British Burma (Myanmar) - Oo, Myo (수완나부미, 2021)
In Myanmar studies, despite research on the categorization of ethnic nationalities are fairly much, research on the categorization of Myanmar people (ethnic Myanmar) is rarely exposed. People settled down in Central Myanmar had been categorized by regionalism into two groups as Anyatha (Upper Lander) and Auktha (Lower lander). It can be determined that the regionalism of Myanmar people existed and still exists. Previous scholarship in the colonial history of Myanmar has primarily referred to the documents recorded by the colonial officers and historical texts composed by the British authorities and scholars. The Catalogue of the Hluttaw Records is one of the rarest documents recorded in the Myanmar language on the affairs in the borderline drawn by the British after the Second Anglo-Myanmar War (1852-1853). Scrutinizing the Catalogue of the Hluttaw Records, it has been found that the text sheds light on the division of Central Myanmar into two regions in colonial Burma, later known as Lower Myanmar and Myanmar kingdom. These areas were known as Upper Myanmar between 1853 and 1885, and the categorization of the Myanmar king's subject, known as Anyatha (Upper Lander) and British colony citizen later known as Auktha (Lower Lander). This article traces back the relation of introducing the colonial boundary system and the division of Central Myanmar into two regions that allowed the emergence of regionalism among Myanmar people.